Análisis de las adaptaciones curriculares aplicadas en estudiantes con discapacidad de educación general básica de escuelas fiscales y particulares del cantón Esmeraldas, periodo de estudio 2012-2013 - Sevilla Gallo, Karol Jessenia (2015)
This thesis presents the results of research, "Analysis of Curricular Adaptations applied to disabled students General Education Basic prosecutors and private schools of Canton Esmeraldas, 2012-2013 study period." It was a qualitative type research, which was attended by authorities, teachers and parents of different fiscal institutions and individuals Canton regular education Esmeralda. It was based major bibliographic sources nationally and internationally allowing knowledge to curricular adaptations are a type of educational strategy generally aimed at students with special educational needs, which consists of adapting the curriculum of a certain educational level in order to make certain content more accessible to a student or a certain type of people or eliminate those elements that will not be achieved by their disability. These take into account the limitations of the student in planning the methodology, content and especially the evaluation. To obtain information applied field research through observation and survey allowing valuable information whose data were tabulated and statistical graphics represented in their analysis. Most teachers in regular education where children are educated (as) and adolescents with disabilities do not apply the appropriate curricular adaptations in the educational process of this population, since it does not have the proper knowledge and preparation to attend and provide education quality for these children. In this investigation followed the guidelines established by the Salesian Polytechnic University